Time-resolved dynamics of thiophene dication – probing parent molecule survival times and multi-step dissociation processes of cyclic molecules by free-electron-laser experiments combined with theoretical simulations. Issue 11 (January 2020) - Kukk, E; Fukuzawa, H; Nagaya, K; Niskanen, J; Luo, Y; Peschel, J; Kooser, K; Itl, E; Pelimanni, E; Saito, S; You, D; Maclot, S; et al.
Synopsis: Thiophene is a cyclic molecule that becomes unstable as a molecular dication. We followed the multi-step dissociation dynamics triggered by soft x-ray FEL pulses from SACLA, core-ionizing the S 2p orbital and creating parent dications by the Auger decay. The time-evolution was probed by optical laser pulsesthat reveal the survival lifetime of the parent dication and the build-up of fragmentation proceeding by ring opening and rupture, accompanied by hydrogen ejection and secondary dissociation. Experimental results are compared to statistical analysis of molecular dynamics simulations.